152 PERFORMANCE OF RISK STRATIFICATION SCORES AND ROLE OF COMORBIDITIES IN OLDER VS YOUNGER PATIENTS WITH PULMONARY ARTERIAL HYPERTENSION. (15th December 2022) - Stolfo, Davide; Barbisan, Davide; Ameri, Pietro; Lombardi, Carlo Mario; Monti, Simonetta; Driussi, Mauro; Zovatto, Isabella Carlotta; Gentile, Piero; Howard, Luke; Toma, Matteo; Pagnesi, Matteo; Collini, Valentino; et al.
Abstract: Background: Risk scores are important tools for the prognostic stratification of pulmonary arterial hypertension (PAH). Their performance and the additional impact of comorbidities across age groups is unknown. Methods: Patients with PAH enrolled from 2001 to 2021 were divided in ≥ 65 years old vs <65 years old patients. Study outcome was 5-year all-cause mortality. FPHN, FPHN non-invasive, COMPERA and REVEAL 2.0 risk scores were calculated and patients categorized at low, intermediate and high risk. Number of comorbidities was calculated. Results: Among 383 patients, 152 (40%) were ≥ 65 years old. Older patients had more comorbidities, with the exception of obesity and diabetes (number of comorbidities 2, IQR 1-3, vs 1, IQR 0-2 in <65 years patients). At 5-year follow-up, 36% of ≥ 65 years patients vs 10% of <65 years patients died. Except for the COMPERA, risk scores correctly discriminated the different classes of risk in the overall cohort and in the older and younger groups. REVEAL 2.0 showed the best accuracy in the total cohort (C-index 0.74) and in younger (C-index 0.72) and older (C-index 0.69) patients. Number of comorbidities was associated with higher 5-year mortality, and consistently increased the accuracy of risk scores, in younger but not in older patients, with the highest accuracy achieved in addition to REVEAL 2.0 (C-index 0.79). Conclusions: Risk scores have similar accuracy in the prognostic stratification of older vs younger PAH patients. REVEAL 2.0 had the best performance in older patients. Comorbidities increased the accuracy of risk scores only in younger patients.